2018
DOI: 10.1039/c7nr06573f
|View full text |Cite|
|
Sign up to set email alerts
|

Nanoparticle binding attenuates the pathobiology of gastric cancer-associatedHelicobacter pylori

Abstract: Enteric bacteria may cause severe diseases, including gastric cancer-associated Helicobacter pylori. Their infection paths overlap with the oro-gastrointestinal uptake route for nanoparticles, increasingly occurring during environmental or consumer/medical exposure. By comprehensive independent analytical methods, such as live cell fluorescence, electron as well as atomic force microscopy and elemental analysis, we show that a wide array of nanoparticles (NPs) but not microparticles form complexes with H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…Several studies reported on the effects of nanoparticles on the surface properties of bacteria and bio‐behaviors in terms of nanoparticles shape, size, and surface charge, Lyden studied the strong electrostatic interaction between hyphae and carboxylate‐functionalized nanoparticles . As shown in Figure 9 A,B, the surface‐absorbed nanoparticles on C. albicans hyphae is evident via electrostatic interaction.…”
Section: Isolation Of Candida Albicans By Electrically Charged Magnetmentioning
confidence: 99%
“…Several studies reported on the effects of nanoparticles on the surface properties of bacteria and bio‐behaviors in terms of nanoparticles shape, size, and surface charge, Lyden studied the strong electrostatic interaction between hyphae and carboxylate‐functionalized nanoparticles . As shown in Figure 9 A,B, the surface‐absorbed nanoparticles on C. albicans hyphae is evident via electrostatic interaction.…”
Section: Isolation Of Candida Albicans By Electrically Charged Magnetmentioning
confidence: 99%
“…We tested NMs varying in size and/or surface functionalization, including NMs that have been proven as reliable models in previous studies, to dene determinants for bacteria-NM interactions and antibiotic effects (Table 1). 13,35,[55][56][57][58] For one, we rst analyzed the interaction of various uorescent polymer and silica NMs with auto-uorescent pathogenic as well as apathogenic bacterial genera in situ using mainly live cell microscopy as a non-invasive method (Fig. 1a, b and e).…”
Section: Resultsmentioning
confidence: 99%
“…Silica, polymer, and metal-based NMs as well as various microparticles were synthesized and provided by the DENANA/ NanoBEL Research consortium, purchased (Merck, Invitrogen, MSC UG) or synthesized as indicated. 22,29,35,[55][56][57][80][81][82] NMs were characterized by EM, DLS, and zeta potential measurements as reported. 55,57,83 Clinical isolates and cultivation of bacteria MDR bacteria were isolated and respective resistance phenotypes characterized at the University Medical Centers of Essen and Mainz using microbial methods as described.…”
Section: Nm Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complicated mutualistic relationships between microbes and their human host, recent changes in human lifestyles due to a greater incorporation of nanotechnology has put significant pressure on the consortia of gut microbiota . Therefore, the exposure to ENMs ( Table 2 ) may modify the composition and diversity of the consortia of the microbiome . The exposure to ZnO NPs (30 nm) for 9 weeks at the dietary dose of 100 mg kg ‐1 altered the richness of the bacterial community and significantly reduced the Lactobacillus in the ileal digesta and plasma metabolites of hens.…”
Section: Enms Induced Perturbations Of Gut Microbiotamentioning
confidence: 99%